2015
DOI: 10.1080/07481187.2015.1068247
|View full text |Cite
|
Sign up to set email alerts
|

The impact of practical support on parental bereavement: Reflections from a study involving parents bereaved through military death

Abstract: This article, drawing on data from a wider study, describes the impact that U.K. bereaved military parents ascribe to the practical support (help with home and garden maintenance) that they received following the death of their son. The type of practical support offered to parents has had a wide-ranging and significant impact on them. In addition to helping them find meaning and maintain continuing bonds, this form of support contributed to their capacity to engage in restoration-focused coping. As a symbolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Research has indicated that that practical support is an important element of the stress process as it aids in relieving distress [64,65]; this facet of support was for not evident in the data. Most participants had some social support in place but lacked the practical support that was needed to overcome the issues that they were facing.…”
Section: Applicationsmentioning
confidence: 85%
“…Research has indicated that that practical support is an important element of the stress process as it aids in relieving distress [64,65]; this facet of support was for not evident in the data. Most participants had some social support in place but lacked the practical support that was needed to overcome the issues that they were facing.…”
Section: Applicationsmentioning
confidence: 85%
“…However, some bereaved parents/grandparents assume custodial care and/or legal guardianship of their orphaned grandchildren, which may lead to financial hardship (Knodel et al., 2007; Lesher & Bergey, 1998; Moore, 2008). New family dynamics and traditions are often embraced as the bereaved parents’ tried to keep the deceased child’s memory alive (Rolls & Harper, 2016; Weed, 2007).…”
Section: Outcomes Of Parental Bereavementmentioning
confidence: 99%
“…Although bereaved parents of Israeli soldiers are honored for their sacrifice, ongoing memorialization and remembrance ceremonies make moving beyond the loss more difficult for grieving parents (Ginzberg et al., 2002; Malkinson & Bar-Tur, 1999; Rubin, 1990). For different reasons, prolonged grief is also common among bereaved parents of veterans in the United Kingdom because in that case, social and governmental support for veteran families is sorely lacking (Rolls & Harper, 2016). In both instances, military protocols regarding notification of the death, death investigation, and release of the body to family can deepen parental devastation (Rolls & Harper).…”
Section: Mediators Of Parental Bereavementmentioning
confidence: 99%
“…Neimeyer’s (2010) concern is that grief could be sustained or increased by the program activities and through contact with other grieving persons. Evaluating bereavement support programs to determine their impact or outcomes is therefore important (DeCinque, Monterosso, Dadd, Sidhu, & Lucas, 2004; Rolls & Harper, 2016; Rolls & Penny, 2011; Valks, Mitchell, Inglis-Simons, & Limpus, 2005; Wilson et al., 2017; Wilson & Playfair, 2016). However, there is no apparent requirement in any country that bereavement programs be evaluated and thus no standards for evaluation frequency or evaluation methods subsequently existing as a consequence.…”
mentioning
confidence: 99%